Broad-spectrum antitumor properties of Withaferin A: a proteomic perspective. Issue 1 (16th December 2019) - Dom, Martin; Vanden Berghe, Wim; Van Ostade, Xaveer
Abstract : A review discussing the broad-spectrum antitumor properties of the natural steroid Withaferin A based on the binding with its true cancer protein targets: a defined stress dependent and stress independent mode of action. Abstract : The multifunctional antitumor properties of Withaferin A (WA), the manifold studied bioactive compound of the plant Withania somnifera, have been well established in many different in vitro and in vivo cancer models. This undoubtedly has led to a much better insight in the underlying mechanisms of WAs broad antitumor activity range, but also raises additional challenging questions on how all these antitumor properties could be explained on a molecular level. Therefore, a lot of effort was made to characterize the cellular WA target proteins, since these binding events will lead and initiate the observed downstream effects. Based on a proteomic perspective, this review provides novel insights in the molecular chain of events by which WA potentially exercises its antitumor activities. We illustrate that WA triggers multiple cellular stress pathways such as the NRF2-mediated oxidative stress response, the heat shock response and protein translation events and at the same time inhibits these cellular protection mechanisms, driving stressed cancer cells towards a fatal state of collapse. If cancer cells manage to restore homeostasis and survive, a stress-independent WA antitumor response comes into play. These include the known inhibition of cytoskeleton proteins, NFκB pathway inhibition and cell cycle inhibition, among others. This review therefore provides a comprehensive overview which integrates the numerous WA–protein binding partners to formulate a general WA antitumor mechanism.